Monoclonal antibodies in COVID-19 management: a scoping review - Adaikkalavan, Umayal; Cherumanalil, Jeeja Mathummal; Pannikkottuthodi, Salwa; Poovancheri, Hasna (International Journal of Basic & Clinical Pharmacology, 2021)
Coronavirus disease 2019 (COVID-19) was declared as pandemic on March 11th 2020 by the world health organization (WHO). Vaccination is for preventing COVID-19 morbidity but when people are infected, treatment is required and even after one and half years the effective cure is yet to be discovered. In this context monoclonal antibodies (mAbs) are promising innovative therapeutic agents in controlling COVID-19 infection. Researchers have found more than 50 mAbs against COVID-19 and they are at different stages of development. Scientists are pacing the research on mAbs. mAbs are innovative therapeutic agents in this context a scoping narrative review was done. At present we have evidences from numerous randomized controlled trials (RCT) on mAbs in effective control of respiratory and coagulation related complications due to COVID-19 infection. Many have got emergency use approval and few of which were withdrawn due to absence of enough evidences or adverse reactions. Examples are bamlanivimab, etesevimab, casirivimab and imdevimab. Other than these many investigational (mAbs) are under scrutiny. With the current evidences the article will give an insight to new and repurposed mAbs which are still under investigation in the management of COVID-19 infections.